2017
DOI: 10.1021/acssuschemeng.6b03105
|View full text |Cite
|
Sign up to set email alerts
|

Role of Alcoholic Hydroxyls of Dicarboxylic Acids in Regulating Nanoscale Dissolution Kinetics of Dicalcium Phosphate Dihydrate

Abstract: Due to the potential shortage of phosphate (P) rock resources and a faster growth in demand for phosphate fertilizers, unraveling the kinetics of calcium phosphate (Ca–P) crystallization and dissolution is important for understanding the P mobility and bioavailability. Plants have developed different strategies, such as carboxylic acid exudation into the rhizosphere, to cope with low P bioavailability through dissolution of sparingly soluble Ca–P minerals. However, the dissolution kinetics may be more complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 61 publications
1
33
0
Order By: Relevance
“…Furthermore, calculated SI also predicts that low concentrations of citrate can promote the formation of strengite, tinticite, or cacoxenite formed on hematite or goethite [5] due to elevated SI (Tables S3 and S4). Organic acids in the soil solution typically range from 0.1 µM to 0.1 mM [5,25,26]. Our experiments also show that higher concentrations of citric acid retard Fe-P precipitation formation.…”
Section: Kinetics and Thermodynamics Of Coupled Dissolution-precipitation At The Iron Oxide-phosphate Solution Interfacesupporting
confidence: 54%
“…Furthermore, calculated SI also predicts that low concentrations of citrate can promote the formation of strengite, tinticite, or cacoxenite formed on hematite or goethite [5] due to elevated SI (Tables S3 and S4). Organic acids in the soil solution typically range from 0.1 µM to 0.1 mM [5,25,26]. Our experiments also show that higher concentrations of citric acid retard Fe-P precipitation formation.…”
Section: Kinetics and Thermodynamics Of Coupled Dissolution-precipitation At The Iron Oxide-phosphate Solution Interfacesupporting
confidence: 54%
“…Despite the presence of repulsive forces, the adsorption of (p)­S­(p)­SEEL to the ACP surface occurs by binding to Ca 2+ sites, and the ACP phase can be stabilized by these negatively charged groups. , For SSEEL, relatively low negative charges result in a decrease of the repulsive force between SSEEL and the HPO 4 2– -enriched ACP. In addition, two hydroxyl groups in two serines and two carboxyl groups in two glutamates of an SSEEL peptide segment enhance the interactions with a HPO 4 2– -enriched hydrated ACP surface, most likely through −OH–Ca 2+ and −COO – –Ca 2+ complexation and H-bonds of −COO – –H 2 O or −OH–OPO 3 H, contributing to the most energetically favorable SSEEL–ACP binding (Figure E). This stronger complexation and chelation with Ca 2+ , from the ACP surface favors the dissolution process. , Promoting the dissolution of the more soluble acidic ACP compared to DCPD by SSEEL may offer a microenvironment to accumulate and rearrange Ca 2+ , resulting in locally higher supersaturation, which would allow the accelerated transformation of ACP to OCP/HAP (Figures and ).…”
Section: Resultsmentioning
confidence: 99%
“…2− -enriched ACP. In addition, two hydroxyl groups in two serines and two carboxyl groups in two glutamates of an SSEEL peptide segment enhance the interactions with a HPO 4 2−enriched hydrated ACP surface, most likely through −OH− Ca 2+ and −COO − −Ca 2+ complexation and H-bonds of −COO − −H 2 O or −OH−OPO 3 H, 36 contributing to the most energetically favorable SSEEL−ACP binding (Figure 4E). This stronger complexation and chelation with Ca 2+37,38 from the ACP surface favors the dissolution process.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…34 This synergistic effect was also observed in dicarboxylic acids with different numbers of alcohol hydroxyls controlling DCPD dissolution by specific molecular recognition and stereochemical conformity between hydroxyl−carboxyl groups of organic acids and atomic steps. 35 The stereochemical relationship and bonding configuration may also account for changes of step kinetics and bulk crystal habits of growing stones. 36 In the present study, we present a comprehensive description of two molecular inhibitors of CA and HCA to modulate the DCPD (010) surface growth using a combination of in situ atomic force microscopy (AFM) and density functional theory (DFT) based molecular modeling.…”
Section: ■ Introductionmentioning
confidence: 99%
“…42 Detailed calculation procedures can be found in our previously published research. 35 ■ RESULTS AND DISCUSSION Effects of HCA and CA on the DCPD (010) Surface Growth. AFM images showed that the growing DCPD (010) surface exhibits typical triangular-shaped hillocks with corresponding step heights of 7.6 Å (Figure 1A), exactly matching theoretical molecular step height.…”
Section: ■ Introductionmentioning
confidence: 99%